1991
DOI: 10.1128/jvi.65.3.1600-1604.1991
|View full text |Cite
|
Sign up to set email alerts
|

Recurring theme of changes in the transcriptional control region of BK virus during adaptation to cell culture

Abstract: BK virus, when cloned directly from human urine, shows no amplification in the transcriptional control region, unlike cell culture-passaged strains, but possesses an additional sequence element. To confirm our proposal that this represents the archetypal in vivo form of the virus, we passaged this BK virus through cell culture. Changes in the transcriptional control region occurred as early as the first passage and were characterized in all cases by a deletion followed by amplification events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The rapid emergence of rr-NCCR BKV variants with higher replicative capacity in immunosuppressed KT patients is reminiscent of rr-NCCR generation in tissue culture ( 26,27,42 ), and is in striking contrast to the stable colonization of the world ' s population with archetype ww-NCCR BKV strains that do not replicate as well ( 43,44 ). Indeed, our ongoing analysis of BKV seropositive healthy blood donors detected asymptomatic BKV viruria in 9.8%, with ww-NCCR in all cases.…”
Section: Discussionmentioning
confidence: 96%
“…The rapid emergence of rr-NCCR BKV variants with higher replicative capacity in immunosuppressed KT patients is reminiscent of rr-NCCR generation in tissue culture ( 26,27,42 ), and is in striking contrast to the stable colonization of the world ' s population with archetype ww-NCCR BKV strains that do not replicate as well ( 43,44 ). Indeed, our ongoing analysis of BKV seropositive healthy blood donors detected asymptomatic BKV viruria in 9.8%, with ww-NCCR in all cases.…”
Section: Discussionmentioning
confidence: 96%
“…The analysis of a fragment of the VP1 coding sequence helps to define the virus genotypes and their different distribution in the human populations [Stoner et al, 2000; Agostini et al, 2001a, b; Pagani et al, 2003; Yogo et al, 2009]. The origin of replication and the promoter region including binding sites for cell transcription factors are located in a region of approximately 400 bp, linked to a non‐coding control region, which may undergo rearrangements easily [Rubinstein et al, 1991; Elsner and Dorries, 1992; Johnsen et al, 1995; Ciappi et al, 1999; Vaz et al, 2000; Rinaldo et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly reported that the predominant NCCR configuration actively shed in urine is archetypal (Markowitz et al, 1991;Negrini et al, 1991;Sharma et al, 2007;Sundsfjord et al, 1999;Takasaka et al, 2004), and that NCCR rearrangements seem to be isolated more frequently from the tissues and sera of patients with high viral loads (Boldorini et al, 2001;Gosert et al, 2008;Stoner et al, 2002). In addition, changes in the NCCR structure arise spontaneously in tissue culture and these rearrangements enhance the ability of the virus to replicate and transform cells (Rubinstein et al, 1991;Watanabe and Yoshiike, 1985;Watanabe and Yoshiike, 1986). It is possible that changes in the viral promoter region can also result in altered pathogenesis, such as a heightened ability to reactivate or disseminate.…”
Section: Introductionmentioning
confidence: 99%